Quantitative genetics in the monk parakeet (Myiopsitta monachus) from central Argentina: Estimation of heritability and maternal effects on external morphological traits. - Juan J Martínez; María C de Aranzamendi; Enrique H Bucher (PLoS ONE)
The monk parakeet (Myiopsitta monachus) is a South American species unique among parrots; it builds communal stick nests that allow independence from tree or cliff cavities required by most parrots. As a very successful invasive species, it has expanded into several countries around the world. Questions remain around the factors that allowed this species to be such a successful invader in its native range as in other countries, and particularly the extent that evolutionary processes may be involved in adapting to new areas. Along with this line of analysis, we focused on assessing whether morphological characteristics are sufficiently heritable, and therefore responsive to selection. As the first step in this direction, we have estimated heritability of monk parakeet in six external morphological traits considered of potential adaptability value. Samples were obtained in the province of Córdoba in central Argentina. Data from seven microsatellites were used to determine the familial relationships among individuals. Heritabilities and genetic correlations were estimated by means of animal models. We found evidence for significant heritability in the six traits measured, particularly in weight, tarsus length and bill width. We also found evidence of maternal effects on morphological traits, particularly in the traits with lower heritability: wing length, bill length and tail length. Genetic correlations between traits were significant and associated with phenotypic correlations, suggesting that these traits are constrained in terms of evolutionary potential, whereas the amount of additive genetic variance in weight, tarsus length and bill width indicate that these traits could be responsive to selection.